Antibiofilm and Antihyphal Activities of Cedar Leaf Essential Oil, Camphor, and Fenchone Derivatives against Candida albicans - Manoharan, Ranjith Kumar; Lee, Jin-Hyung; Lee, Jintae (Frontiers in Microbiology, 2017)
Candida albicans can form biofilms composed of yeast, hyphal, and pseudohyphal elements, and C. albicans cells in the hyphal stage could be a virulence factor. The present study describes the chemical composition, antibiofilm, and antihyphal activities of cedar leaf essential oil (CLEO), which was found to possess remarkable antibiofilm activity against C. albicans but not to affect its planktonic cell growth. Nineteen components were identified in CLEO by gas chromatography/mass spectrometry, and phenolics were the main constituents. Of these, camphor, fenchone, fenchyl alcohol, α-thujone, and borneol significantly reduced C. albicans biofilm formation. Notably, treatments with CLEO, camphor, or fenchyl alcohol at 0.01% clearly inhibited hyphal formation, and this inhibition appeared to be largely responsible for their antibiofilm effects. Transcriptomic analyses indicated that camphor and fenchyl alcohol downregulated some hypha-specific and biofilm related genes (ECE1, ECE2, RBT1, and EED1). Furthermore, camphor and fenchyl alcohol reduced C. albicans virulence in a Caenorhabditis elegans nematode model. These results demonstrate CLEO, camphor, and fenchyl alcohol might be useful for controlling C. albicans infections.